Economical Order Quantity, Safety Stock, dan Reorder Point pada Raw Inventory - Juniaty Ismail (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This research was conducted with the aim to find out how the management ofinventories of raw materials in UKM FM in times of scarcity and rising rawmaterial prices. The difference between this study and previous studies is thatthe focus of the research is on small and medium enterprises that do notunderstand how to properly manage raw materials. In this study the authorswere directly involved in the observation and interview, so that the datacollected is completely accurate according to research needs. The steps of datacollection including observation, interviews and documentation. The dataanalysis technique used is descriptive qualitative method with EOQ analysis.The results showed that UKM FM in producing its products primarily shreddedfish often run into obstacles that the scarcity of raw materials of fish when theweather is bad, so the level of demand for such raw materials as well asproduction processes become inhibited. Moreover, scarcity of raw materials thatcontributed to rising prices of raw materials and consequently also influence theselling prices come down in consumer demand. To overcome this, the UKM FMdo it with EOQ Analysis, Safety Stock and Reorder Point approach.